ACADEMIC WRITING 2.0: STUDENTS’ PERCEPTIONS ON ACADEMIC WRITING WITH BLENDED LEARNING MODE IN UNIVERSITY CURRICULUM - Suzanna Alwasilah, Senny (SAMPURASUN, 2024)
This research explores students' perceptions of implementing a Blended Learning model in an academic writing course to address challenges in foreign language academic writing. 40 respondents participated, and mixed-methods, including WEBLEI Survey and Case Study 2.0 frameworks, were employed. Data collection involved tests, surveys, asynchronous interviews, and Focus Group Discussions. Statistical analysis indicated positive student attitudes, with mean scores for Interaction, Access, Response, and Result on the WEBLEI Scale being 3.85, 4.12, 4.07, and 4.10, respectively. Results suggest that students benefitted from flexibility in learning processes, access to learning, satisfaction with the learning environment, and pace of learning in the Blended Learning model.